Strategi Komunikasi Kesehatan dalam Upaya Membangun Partisipasi Publik pada Masa Pandemi Covid-19 - Silvia Nevane Paramasari; Adi Nugroho (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Health communication is a systematic effort that has a positive impact on the health practice of a large population. The Covid-19 pandemic, which is felt quite suddenly, caused confusion from all sectors, one of which is the health sector. The health sector in Indonesia looks unprepared for this pandemic in communicating the Covid-19 virus to the public. Therefore, health communication, which is part of mass communication, is one of the communication models that can give information the public about health. The focus in this research is on health communication strategies during the COVID-19 pandemic. The research method used in this research is literature study. The result and conclusion of this study which is the health communication strategy in building public participation during the covid-19 pandemic is 1) health communication campaigns must be carried out in an integrated and sustainable manner and carried out by experts, 2) creating and implementing appropriate and effective communication strategies in handling Covid-19, 3) developing appropriate, effective and efficient tactics and technical actions and procedures